1997
DOI: 10.1046/j.1365-2567.1997.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipids from Mycobacterium leprae cell wall suppress T‐cell activation in vivo and in vitro

Abstract: SUMMARYThe influence of Mycobacterium leprae cell wall lipids on lymphocyte functions has been investigated in vivo (delayed-type hypersensitivity) and in vitro. The inflammatory response has been earlier evaluated by the mouse footpad oedema model and the delipidated mycobacteria evoked a mild but significant inflammatory response. Herein a higher level of hypersensitivity reaction was observed with delipidated bacilli than with the intact mycobacteria. The lipids obtained from the extract of M. leprae extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Thus, the chemical basis of this cross-reactivity between DAT and M. leprae cells is of great interest. For instance, the presence of DAT in M. leprae cells could also account for some immunosuppressive effects reported in LAM-and phenolic glycolipid-free lipid extracts obtained from this species (30).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the chemical basis of this cross-reactivity between DAT and M. leprae cells is of great interest. For instance, the presence of DAT in M. leprae cells could also account for some immunosuppressive effects reported in LAM-and phenolic glycolipid-free lipid extracts obtained from this species (30).…”
Section: Discussionmentioning
confidence: 99%
“…Two of these, with molecular masses of 47 and 84 kDa, were found to elicit strong serum IgG responses in humans following infection, including sera from volunteers who were immune to C. jejuni infection when rechallenged. Capsular polysaccharide antigens, the basis of the Penner serotyping scheme, are also immunogenic, eliciting both type-specific and cross-reactive responses (114,144). The CDT produced by Campylobacter is also immunogenic in human infections, eliciting toxin-neutralizing antibodies (1).…”
Section: Humoral Immunity To Campylobactermentioning
confidence: 99%
“…Recently, it has been reported that mycobacterial lipids indirectly inhibit T cell mitogenesis by infected macrophages [5,10,17,18,27]. Phosphatidylserine collaborates with reactive nitrogen intermediates and TGFb, pointing to the essential role of these structures in macrophage function [10,27].…”
Section: Discussionmentioning
confidence: 99%
“…These liposomes were prepared for the biological assays as a control for LE and for LBCG as previously described [16,17]. Briefly, cholesterol (Sigma) and phosphatidylcholine (Sigma) both at 10 mM in chloroform were mixed in a molar ratio of 2 : 7.…”
Section: Liposomes Prepared From Cholesterol-choline (Cc)mentioning
confidence: 99%
See 1 more Smart Citation